Immunomodulatory effects of cigarette smoke condensate in mouse macrophage cell line. (September 2017) - Zhao, Junwei; Li, Xiang; Xie, Fuwei; Yang, Zhihua; Pan, Xiujie; Zhu, Maoxiang; Shang, Pingping; Nie, Cong; Liu, Huimin; Xie, Jianping
Increasing evidence has demonstrated that the secretion of cytokines may be associated with cigarette smoke–induced immunomodulatory effects, but a comprehensive analysis of the cytokine profile for cigarette smoke condensate (CSC) exposure is lacking. The aims of this study were to (1) examine the release of 20 cytokines induced by CSC from 12 brands of cigarettes in macrophages cells (Ana-1) and (2) to investigate the general characteristics of the immunomodulatory effects of CSC. Luminex technology was used to simultaneously determine the levels of 20 cytokines (interleukin (IL)-1α, IL-1β, IL-2, IL-4, IL-5, IL-6, IL-10, IL-12, IL-13, IL-17, granulocyte-macrophage colony-stimulating factor (GM-CSF), interferon-γ (IFN-γ), keratinocyte-derived Chemokine (KC), monocyte chemoattractant protein 1 (MCP-1), macrophage inflammatory protein 1α (MIP-1α), induced protein 10 (IP-10), tumor necrosis factor α (TNF-α), vascular endothelial growth factor (VEGF), monkine inducible by γ interferon (MIG), and fibroblast growth factor (FGF)-basic) in the supernatants from Ana-1 cells treated with the CSC. The results showed that the release of eight cytokines was altered (IL-5, IL-6, IL-12, TNF-α, VEGF, IP-10, MCP-1, and MIP-1α) compared with the control. These cytokines fall into two major subtypes: proinflammatory cytokines, including IL-5, IL-6, IL-12, TNF-α, and VEGF, and chemokines, including IP-10, MCP-1, and MIP-1α. Compared with control, the remaining 12 cytokines were not significantly affected by CSC from the 12 brands of cigarettes. As a general characteristic, CSC exerts potently suppressive immunomodulatory effects on cytokine production of Ana-1 cells. Proinflammatory cytokines and chemokines may account for or contribute to the immunosuppressive properties of CSC.